Impact of preoperative vaginal preparation with povidone iodine on post cesarean infection - Shahnaz Barat; Zinatossadat Bouzari; Azita Ghanbarpour; Zeinab Zabihi (Babol University of Medical Sciences, 2016)
Background: Obtaining clinical methods in order to decrease the infectious morbidity of cesarean delivery is very important.  The aim of this study was to determine the effect of preoperative vaginal preparation with antiseptic solution on post-caesarean infections. Methods: This study was conducted on 400 singleton term pregnant women undergoing elective cesarean delivery. The samples were randomized into two groups; experimental group, including women who received an additional preoperative vaginal cleansing with 10% povidone iodine; and a control group, including women who received only the standard abdominal preparation. All subjects received a single dose of prophylactic antibiotic and were investigated after cesarean delivery until the 6th postoperative weeks for postoperative fever, wound infection, or endometritis. Data were analyzed using SPSS software and the P value < 0.05 was considered significant. Results: The groups were similar in age, education level, body mass index, and parity. The operation variables such as the postoperative fever, wound infection, and endometritis were observed in the two groups, and the overall for these were found to be 6.0 %, 6.3%, and 6.5%, respectively. A total of 7.5% of the participants in the control group and 5.5% of the participants in the experimental group developed postoperative endometritis; but it was not statistically significant (relative risk= 0.86; 95% confidence interval, 0.61 -1.21; P=0.417). Also, there was no significant difference in postoperative fever, wound infection between these women with and without preoperative vaginal cleansing with povidone. Conclusion: The findings of the present study indicated that vaginal cleansing with povidone iodine immediately prior to elective cesarean delivery did not decrease the post-caesarean infection rates and the incidence of endometritis in low-risk women.